Development of Physical and Self-Control Abilities of Junior Schoolchildren (10–11 Years Old) (Baltic Journal of Sport and Health Sciences, 2014)
Background. The goal of the research is to reveal the dynamics in physical abilities of junior school learners (10–11 years old) and their links with development of self-control abilities by applying the programme for development of self-control abilities in physical education classes during the experimental period. The pedagogical experiment was carried out with 4th forms of general education schools of Klaipėda, Kaunas and Raseiniai from 2011 to 2012 and lasted for one school year. The research included 178 school learners in the experiment group (n = 85) and in the control group (n = 93).Methods. The questionnaire method was applied to evaluate the change in self-control abilities, whereas the testing method was used to identify the change in physical abilities (flexibility, explosive power, agility, speed, balance, abdominal muscle strength and stamina).Results. Statistically significant differences were identified among boys from the experimental and the control groups considering the results of flexibility, long jump, abdominal muscle strength and stamina (p < .01), dexterity and speed (p < .05) and among girls when measuring the results of flexibility, long jump, speed, balance, abdominal muscle strength and stamina (p < .01). Application of Pearson’s correlation, correlating links between the abilities of physical and psychosocial self-control, revealed that school learners with better abilities of psychosocial self-control also demonstrated a number of better physical abilities: linear correlation links were established between psychosocial control and flexibility, explosive power, speed, stamina and balance abilities. These links showed that improvement of self-control skills had an effect on self-development of physical abilities.Conclusion. The research has revealed a positive impact of the programme due to which development of self-control abilities determined a change in physical abilities.Keywords: self-control, physical abilities, junior schoolchildren.